2019
DOI: 10.1177/0021998319890405
|View full text |Cite
|
Sign up to set email alerts
|

Continuous ultrasonic welding of thermoplastic composites: Enhancing the weld uniformity by changing the energy director

Abstract: Continuous ultrasonic welding is a high-speed joining method for thermoplastic composites. Currently, a thin film energy director is used to focus the heat generation at the interface. However, areas of intact energy director remain in the welded seam, which significantly lowers the weld strength, and result in a non-uniformly welded seam. To improve the weld uniformity of continuous ultrasonically welded joints, we changed to a more compliant energy director. A woven polymer mesh energy director was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 16 publications
(39 reference statements)
0
26
0
Order By: Relevance
“…Triangular protrusions are typically employed in the plastics industry, but for continuous fiber-reinforced thermoplastics, thin films are also suitable and lead to high strength welds [ 14 , 15 , 16 , 17 , 18 ]. Many studies in the literature experimentally investigated the effect of process parameters (amplitude, force and control mode) and ED geometry on bond quality [ 10 , 14 , 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] and heat generation [ 18 , 27 , 28 ]. For instance, it was reported that using the vertical displacement of the sonotrode could lead to consistent weld quality using power and displacement curves from the welder.…”
Section: Introductionmentioning
confidence: 99%
“…Triangular protrusions are typically employed in the plastics industry, but for continuous fiber-reinforced thermoplastics, thin films are also suitable and lead to high strength welds [ 14 , 15 , 16 , 17 , 18 ]. Many studies in the literature experimentally investigated the effect of process parameters (amplitude, force and control mode) and ED geometry on bond quality [ 10 , 14 , 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] and heat generation [ 18 , 27 , 28 ]. For instance, it was reported that using the vertical displacement of the sonotrode could lead to consistent weld quality using power and displacement curves from the welder.…”
Section: Introductionmentioning
confidence: 99%
“…Heat generation is focused at the weld interface by means of an energy director (ED) placed in between the adherends [17,19]. This ED consists of either one or more resin protrusions moulded on the surface of one of the adherends [20][21][22] or a loose resin-rich layer such as a film (also referred to as flat ED) [19,23] or a woven mesh [14,24] made from the same polymer material as that in the adherends. Due to the lower compressive stiffness of the ED compared to that of the fibre reinforced adherends, the ED undergoes higher cyclic strains and it therefore generates more heat than the adherends [22,25].…”
Section: Introductionmentioning
confidence: 99%
“…Sequential application of this static process allows obtaining multi-spot welded joints that can match load carrying capabilities of mechanically fastened joints [26,27]. The continuous ultrasonic welding process (Figure 1b) is defined as follows: a relatively large area is welded by continuously translating the welder with respect to the adherends or vice versa while exerting the ultrasonic vibrations and welding pressure [14,24]. Since the sonotrode continuously moves away from the just welded area, an additional consolidation shoe (consolidator) needs to be placed behind the sonotrode to allow the weld to cool down under pressure [15].…”
Section: Introductionmentioning
confidence: 99%
“…double cantilever beam test coupons, relatively complex experimental set-ups need to be built in which an end effector with heating and pressure application capabilities is automatically translated along the area to be welded [1416]. Furthermore, the addition of this extra degree of freedom requires, on some occasions, a substantial redefinition of the basic aspects of the welding process itself [17,18].…”
Section: Introductionmentioning
confidence: 99%